2017
DOI: 10.1007/s00221-017-4925-4
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the reach and grasp in head-fixed vs freely-moving mice provides support for multiple motor channel theory of neocortical organization

Abstract: Multiple motor channel (MMC) theory of neocortical organization proposes that complex movements, such as reaching for a food item to eat, are produced by the coordinated action of separate neural channels. For example, the human reach-to-grasp act is mediated by two visuo-parieto-motor cortex channels, one for the reach and one for the grasp. The present analysis asked whether there is a similar organization of reach-and-grasp movements in the mouse. The reach-to-eat movements of the same mice were examined fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…First, we found that reach endpoint appears to be actively regulated in trials in which animals make several attempts during a single reach. A previous study reported multiple-attempt reaches in head-fixed mice, describing a touchrelease-grab sequence in which the initial attempt involves "semi-flexed and semi-closed digits" (Whishaw et al, 2017). We extended this observation by analyzing endpoints on subsequent reach attempts, finding that the mean distance from the target decreased from first to second attempts with no significant difference in endpoint variability.…”
Section: Regulation Of Motor Variabilitymentioning
confidence: 55%
See 3 more Smart Citations
“…First, we found that reach endpoint appears to be actively regulated in trials in which animals make several attempts during a single reach. A previous study reported multiple-attempt reaches in head-fixed mice, describing a touchrelease-grab sequence in which the initial attempt involves "semi-flexed and semi-closed digits" (Whishaw et al, 2017). We extended this observation by analyzing endpoints on subsequent reach attempts, finding that the mean distance from the target decreased from first to second attempts with no significant difference in endpoint variability.…”
Section: Regulation Of Motor Variabilitymentioning
confidence: 55%
“…Thus, charting similarities and differences in basic kinematic measurements across behavioral contexts and across species can provide stepping stones for future experiments aimed at uncovering neural mechanisms into how the nervous system produces reach behavior. Although some prior studies quantified aspects of mouse reach kinematics, the majority focused mainly on success rates, qualitative descriptions and scoring systems, or categorical demarcation of the reach into phases, with few explicit connections drawn to the kinematic control principles discussed here (Esposito et al, 2014;Farr & Whishaw, 2002;Galiñanes et al, 2018b;Guo et al, 2015;Whishaw, 1996;Whishaw et al, 2017Whishaw et al, , 2018Whishaw & Pellis, 1990). This study establishes several basic quantitative frameworks for analyzing mouse reach kinematics, allowing numerical comparisons to be drawn across species and across tasks.…”
Section: Comparative Kinematics Support Reach Homology Across Speciesmentioning
confidence: 90%
See 2 more Smart Citations
“…To assess the effect of physostigmine injections on the quality of reaches, the video recordings on day 9 , from the first 3 reaches, 12 components of movements were scored on a 0, 0.5, and 1 scale (good, impaired, and absent performance). A higher score thus indicates inferior performance (Whishaw IQ et al 2008;Whishaw IQ et al 2017). To compare scores of the two groups, we performed repeated measures ANOVA with Treatment (Saline or Physostigmine) and Sex as "between-subjects" factors and Movement Inayat_and_Qandeel et al 2019…”
Section: A Rotarod Task -Experimental Setup and Behavioral Protocolsmentioning
confidence: 99%